1973
DOI: 10.21236/ada037323
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Related to Premature Attrition of Navy Recruits

Abstract: The problem of turnover has become one of major importance to both Industry and the milItary. The costs of even a small turnover are great In terms of money, personnel utilization, training, and time, The frustration experienced by those who leave an organization, as well as that felt by those-who failed In their performance of selecting and training these Individuals, results In a huge waste of human energy. The reduction In turnover would Improve any organization's program of human utilization and also Its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several studies have shown that self-reported past expulsions or suspensions from school were risk factors for attrition (20,106,153,154,199). Studies that have performed multivariate analysis have found that expulsions from school independently increased the risk of first-temi attrition when other potential attrition risk factors were included in the model such as demographics, service satisfaction variables, education, family stability measures, physical health measures, and cognitive test scores (20,153,154,199), Other risk factors for basic training attrition included self-reports of being charged with or suspected of a crime (106), traffic violations, times late for school (153), fighting while intoxicated, rebelliousness (244), and being arrested for a crime (20,154,253).…”
Section: (2) Moral Charactermentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that self-reported past expulsions or suspensions from school were risk factors for attrition (20,106,153,154,199). Studies that have performed multivariate analysis have found that expulsions from school independently increased the risk of first-temi attrition when other potential attrition risk factors were included in the model such as demographics, service satisfaction variables, education, family stability measures, physical health measures, and cognitive test scores (20,153,154,199), Other risk factors for basic training attrition included self-reports of being charged with or suspected of a crime (106), traffic violations, times late for school (153), fighting while intoxicated, rebelliousness (244), and being arrested for a crime (20,154,253).…”
Section: (2) Moral Charactermentioning
confidence: 99%
“…Studies that have performed multivariate analysis have found that expulsions from school independently increased the risk of first-temi attrition when other potential attrition risk factors were included in the model such as demographics, service satisfaction variables, education, family stability measures, physical health measures, and cognitive test scores (20,153,154,199), Other risk factors for basic training attrition included self-reports of being charged with or suspected of a crime (106), traffic violations, times late for school (153), fighting while intoxicated, rebelliousness (244), and being arrested for a crime (20,154,253). Self-reported fighting while intoxicated was an independent risk factor for psychiatric/behavioral and legal discharges but not medical or inadequate performance discharges (244), Self-reported rebelliousness was an independent risk factor for attrition of all types (244), Self-reported arrest for a crime was independently related only to behavioral attrition (20).…”
Section: (2) Moral Charactermentioning
confidence: 99%
See 2 more Smart Citations
“…The 17 items form a stress-linked cluster reflecting nervousness and emotionality. This cluster has been shown to predict attrition of Navy recruits for reason of inaptitude, enuresis, or character and behavior disorder (Hoiberg, Hysham, & Berry, 1973).…”
mentioning
confidence: 96%